1947
DOI: 10.1021/ie50447a626
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Organic Compounds in Liquid Hydrogen Fluoride

Abstract: Perfluoro-1,3-dimethylcyclohexane 99-100 400 395 Usil3ir,7(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1969
1969
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Numerous experimental results supported this mechanism. Several research groups observed that dehydrogenation of certain aromatic compounds can occur not only in the presence of AlCl 3 and similar Lewis acids, but also in media such as anhydrous HF34, 35 or PhSO 3 H,30 while radical cations cannot be formed under such conditions. Baddeley and Kenner observed that the presence of hydrogen chloride is essential for the synthesis of benzanthrone ( 11 ) to occur 29.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Numerous experimental results supported this mechanism. Several research groups observed that dehydrogenation of certain aromatic compounds can occur not only in the presence of AlCl 3 and similar Lewis acids, but also in media such as anhydrous HF34, 35 or PhSO 3 H,30 while radical cations cannot be formed under such conditions. Baddeley and Kenner observed that the presence of hydrogen chloride is essential for the synthesis of benzanthrone ( 11 ) to occur 29.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…A combined addition-elimination mechanism results finally in the total displacement of fluorine and the formation of a carboxylic group [391]. (223) Strong acids hydrolyze the trifluoromethyl group to a carboxylic group under vigorous conditions [392][393][394]. …”
Section: Hydrolysis Of Difluoromethylene Groupmentioning
confidence: 99%
“…Zahlreiche experimentelle Befunde stützten diesen Mechanismus. Mehrere Gruppen beobachteten, dass eine Dehydrierung bestimmter aromatischer Verbindungen nicht nur in Gegenwart von AlCl 3 und ähnlichen Lewis‐Säuren auftreten kann, sondern auch in Medien wie wasserfreiem HF34, 35 oder PhSO 3 H,30 während Radikalkationen unter solchen Bedingungen nicht gebildet werden können. Baddely und Mitarbeiter beobachteten, dass die Anwesenheit von Chlorwasserstoff für die Synthese von Benzanthron ( 11 ) essenziell ist 29.…”
Section: Mechanistische üBerlegungenunclassified